Emotional labor, occupational identity and work engagement in Portuguese police officers - Oliveira, Soraia (2023)
Based on emotional labor theory, we aim to study the relationships between the dimensions of emotional labor (requirements and strategies), work engagement, and occupational identity in Portuguese police officers. Therefore, we intend to explore the possible effects of emotional labor both on work engagement and occupational identity, as well as ways of preventing and/or mitigating the impact of these relationships. We identified a gap in the studies on this subject in Portugal, particularly in the context of police professionals. Thus, a sample of 924 Portuguese police officers of the Public Security Police (PSP) was asked to answer a set of questionnaires: the Emotional Labour Scale, the Emotion Work Requirements Scale, the Utrecht Work Engagement Scale, and the Social Identity Scale. The data obtained was analyzed using correlation and multiple linear regression. Overall, the results revealed relationships between the emotional demands (i.e., suppression of negative emotions and expression of positive emotions) and strategies (i.e., deep and surface acting) of emotional labor and work engagement as well as occupational identity. We discuss these results and propose directions for future research, given the richness of the subject.